Academic libraries in Massive Open Online Courses (MOOCs): The challenges - Ibrahim, Shahril Effendi (Persatuan Pustakawan Malaysia, 2014)
The emergence of MOOCs cannot be ignored especially among academic librarians. The involvement of librarians in this worldwide open access movement is essential to realise the democratisation of higher education. This paper describes the concept and development of MOOC in previous years. It also highlights the structure and features of MOOC. It explains the challenges and roles of academic librarians in providing the best services to the MOOC environment and community. The paper also will briefly discuss the future of MOOC and the implementation of MOOC in Malaysia and in Open University Malaysia (OUM).